2019
DOI: 10.1177/0733464819832198
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease Self-Management Among Iranian Older Adults: A Scoping Review

Abstract: Background: Implementing care models that emphasize chronic disease self-management (CDSM) strategies may be an effective approach to the growing prevalence of chronic conditions in Iran. We, therefore, conducted a scoping review on CDSM among older Iranians to identify existing gaps and opportunities to improve chronic disease care. Method: We conducted a search in CINAHL, EMBASE, MEDLINE/PubMed, and Cochrane library. Selected articles were charted based on year of publication, language, objectives, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Chronic disease self-management (CDSM) involves daily strategies an individual uses to control their diseases [ 8 ], such as exercise, diet, health checkups, and medication. Interventions targeting self-management are effective and affordable, gaining worldwide attention [ 9 , 10 ]. Therefore, instead of implementing financially constrained models and medically resource-constrained models, CDSM can be used to improve the health status and quality of life and reduce the incidence of complications in older adults with CNCDs [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic disease self-management (CDSM) involves daily strategies an individual uses to control their diseases [ 8 ], such as exercise, diet, health checkups, and medication. Interventions targeting self-management are effective and affordable, gaining worldwide attention [ 9 , 10 ]. Therefore, instead of implementing financially constrained models and medically resource-constrained models, CDSM can be used to improve the health status and quality of life and reduce the incidence of complications in older adults with CNCDs [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing number of scoping reviews have been published worldwide for various purposes, mainly on health topics (3). In Iran, some scoping reviews have been conducted on medical subjects, such as chronic diseases or tobacco control; however, none of them has addressed AMR (6,7). A national survey on healthcare-associated infections in Iran showed that the pattern and severity of AMR in different provinces are different.…”
Section: Contextmentioning
confidence: 99%
“…Repeated hospitalization, coughing and sputum, dyspnoea, reduced self‐care ability and limited social activities are characteristics of COPD patients, and COPD patients are prone to manifestations of low spiritual health such as doubting the value of life, helplessness and despair as result, leading to a lower level of quality of life for patients (da Silva et al, 2009; Giacomini et al, 2012; Maddocks et al, 2017). Spiritual health falls under the umbrella of successful ageing (Zarrin et al, 2020), and older people with COPD necessarily need to cope with spiritual health issues such as death and meaning of life as a result of ageing (Hupkens et al, 2018; Zhang et al, 2019). Therefore, attention to the spiritual health of older COPD patients and its associated factors is particularly important for improving quality of life and achieving successful ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Fisher et al (2000) defined spiritual health as an individual's exploration of the meaning and purpose of life in dealing with relationships with self, community, environment and the transcendental, and seeking self‐integration, leading to a state of inner peace and comfort. Spiritual health is not only recognized by the World Health Organization (WHO) as the fourth dimension of health and a facilitator of successful ageing (Dhar et al, 2013; Zarrin et al, 2020), it is also an important component of chronic disease self‐management and healthy ageing (Gijsberts et al, 2019; Jaberi et al, 2019; Zarrin et al, 2020). The role of spiritual health in the management of COPD chronic disease has been gradually recognized in the last decade (Gergianaki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%